West Nile virus lineage 2 isolated from Culex modestus mosquitoes in the Czech Republic, 2013: expansion of the European WNV endemic area to the North? - Rudolf, I; Bakonyi, T; Sebesta, O; Mendel, J; Peško, J; Betášová, L; Blažejová, H; Venclíková, K; Straková, P; Nowotny, N; Hubálek, Z (Euro surveillance, 2014)
We report the detection and isolation of four almost identical strains of West Nile virus (WNV) lineage 2from Culex modestus mosquitoes collected at three fish ponds in South Moravia, Czech Republic, during August 2013. Phylogenetic analysis demonstrated that the Czech WNV strains isolated are closely related to Austrian, Italian and Serbian strains reported in 2008,2011 and 2012, respectively. Our findings show the current northernmost range of lineage 2 WNV in Europe.
Keywords: Molecular Sequence Data; Italy; Prevalence; Endemic Diseases; endemické nemoci; Europe; West Nile virus; Česká republika; Evropa; prevalence; RNA, Viral; Culex; Czech Republic; Culicidae; západonilská horečka; Insect Vectors; zvířata; fylogeneze; Itálie; molekulární sekvence - údaje; hmyz - vektory; virus západního Nilu; Phylogeny; West Nile Fever; RNA virová; Animals